IMPACT OF RELIGIOUS ORIENTATION AND LIFE SATISFACTION ON DEATH ANXIETY AMONG ADOLESCENTS - Yameen, Ayesha; Iftikhar, Lubna (PEOPLE: International Journal of Social Sciences, 2018)
The present study was co- relational and aimed to analyze the impact of religious orientation and life satisfaction on death anxiety among university students. It further explored the relationship between life orientation skills and religious orientation together with their differences in relation to gender. Scales used in the study to collect data were Life Satisfaction Scale, Death Anxiety Scale and Religious Orientation Scale. Data was gathered by convenient sampling of 150 university students (75 males, 75 females). Their age and educational qualifications were restricted to 20-23 years and masters respectively. The results revealed that both interaction of religious orientation and life satisfaction were significant predictor of death anxiety (F=1.43, p>0.01) among university students. The correlation between religious orientation and life satisfaction was found to be positive and male adolescents were found to have higher religious orientation, life satisfaction and lower levels of death anxiety as compared to females.